Dinamika partai politik Indonesia dilihat dari sudut pandang historiografi - Wakindiyah, Nimas Yuhyih (Maliki Interdisciplinary Journal, 2023)
The system in Indonesia has been formed since 1945, by going through a long journey of government from the colonialists. Indonesia's founding fathers then formed a central government as a form of effort to unite people from various religious and cultural backgrounds. In Indonesia, political parties are infrastructure in the country's political system. Historically, political parties have been used as a forum for the struggle of independence figures against the resistance of the colonialists. The purpose of writing this article is to describe the history of Indonesian political parties and their role from time to time, starting from the New Order, Old Order to the reformation period. This article also includes an analysis of the problems and interpretation using descriptive analysis method. The result of the study of this article is that in practice, political parties have the power of every state policy. In its travel concept, the concept of representative raises doubts in the hands of political parties. It is then that the state must review whether the country's political system is in accordance with the Constitution and Pancasila as the basis of the Republic of Indonesia.